2008
DOI: 10.1074/jbc.m805927200
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α Is Essential for Normal Intrauterine Differentiation of Alveolar Epithelium and Surfactant Production in the Newborn Lung of Mice

Abstract: Neonatal respiratory distress syndrome (RDS) is mainly the result of perturbation in surfactant production and is a common complication seen in premature infants. Normal fetal lung development and alveolar cell differentiation is regulated by a network of transcription factors. Functional loss of any of these factors will alter the developmental program and impact surfactant production and normal gas exchange. During development, the fetus is exposed to varying oxygen concentrations and must be able to quickly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 29 publications
3
72
1
Order By: Relevance
“…The loss of HIF1a early in murine lung development in utero leads to pups that die within hours of birth, with symptoms similar to those of neonatal respiratory distress syndrome (16). The lungs of these pups exhibited impaired alveolar epithelial differentiation and an almost complete loss of surfactant protein expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of HIF1a early in murine lung development in utero leads to pups that die within hours of birth, with symptoms similar to those of neonatal respiratory distress syndrome (16). The lungs of these pups exhibited impaired alveolar epithelial differentiation and an almost complete loss of surfactant protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…In alveolar epithelial cells, HIF 1a and HIF2a are expressed, and both are regulated by hypoxia (8,(10)(11)(12)(13). HIF is also important at physiologic levels of hypoxia, for example, in tumors (where it is responsible for the Warburg effect [aerobic glycolysis]) (14), in the normal liver (15), in fetal lung (16), and in inflammatory exudates (17), as well as in severe hypoxia (1% oxygen) (12).…”
mentioning
confidence: 99%
“…In contrast, differentiation and development of the fetal lung distal epithelium normally occurs in low O 2 (1-5% O 2 ) (19), with hypoxia-related signaling in the pulmonary epithelium throughout gestation (8,9,28). This condition is critical for normal fetal lung development and preparation for breathing after birth (1,32). Thus, elucidating the molecular mechanisms of pulmonary adaptations to low O 2 tension is of particular clinical significance for understanding both lung pathology and normal development.…”
mentioning
confidence: 99%
“…HIFs are heterodimer complexes constituted by two subunits (Groenman et al, 2007). When exposed to low oxygen, the alpha-subunit which is easily degraded in normoxia accumulates, binds to the beta-subunit and transactivates multiple downstream genes which contain the hypoxia response elements and are involved in embryonic development (Saini et al, 2008). Our study also demonstrated that this mechanism may work in the thyroid differentiation.…”
Section: Discussionmentioning
confidence: 56%